Assessing Domestic vs. International Student Perceptions and Attitudes of Plagiarism - Doss, Daniel Adrian; Henley, Russ; Gokaraju, Balakrishna; McElreath, David; Lackey, Hilliard; Hong, Qiuqi; Miller, Lauren (Journal of International Students, 2016)
The authors examined students’ perceptions of plagiarism from a higher education teaching institution within the U.S. southeast. This study employed a five-point Likert-scale to examine differences of perceptions between domestic versus international students. Statistically significant outcomes were observed regarding the notions that plagiarism is a necessary evil and that plagiarism is illegal. Respectively, the analyses of the means showed that respondents tended toward disagreement concerning the former notion and neutrality regarding the latter notion.